Recurrent Orthodromic SVT AVRT with Multiple Accessory Pathway in WPW syndrome: Ablate All or Not? - Aziz, Indra Jabbar; Rizal, Ardian (Heart Science Journal, 2024)
Background: Patients diagnosed with Wolff-Parkinson-White syndrome (WPW) have a relatively low, nevertheless persistent risk of unexpected mortality. However, this risk can be effectively mitigated by applying radiofrequency catheter ablation targeting the accessory pathway. It is difficult to accurately study predictors because only a minority of patients develop potentially malignant arrhythmias (MA) or passed away, despite essential risk variables being relatively well-known.1 This study aimed to describe ablation in WPW syndrome.Case presentation: A 16-year-old male presents with symptoms characterized by palpitations during intense physical exertion, followed by chest pain episodes. The physical examination, CXR, laboratorium, and echocardiography were all within the normal range; his ECG showed shortened PR interval and a delta wave with a positive delta wave at V1 and mostly positive at the inferior lead. He also has recorded ECG when the patient has a tachycardia event with SVT AVRT orthodromic pattern. He underwent EP Study and had several accessory pathways at the posteroseptal mitral annulus and anteroseptal tricuspid. The decision was made to perform ablation on the posteroseptal accessory pathway located at the mitral annulus. An electrophysiology (EP) investigation was conducted at the anteroseptal tricuspid annulus, which did not induce tachyarrhythmia.Conclusion: Wolff-Parkinson-White syndrome is a congenital cardiac pathway formation, with not all accessory pathways causing tachyarrhythmias. Ablation therapy is necessary for patients with multiple pathways, with pathways with an ERP less than 250 being the only option.